Pengetahuan Bencana Banjir Terhadap Kesadaran Lingkungan Siswa Sekolah Menengah Atas - Syahrul Januar Primaditya; Dewi Liesnoor Setyowati; Hariyanto; Tjaturahono Budi Sanjoto; Erni Suharini (Jurnal Penelitian Pendidikan Geografi, 2024)
Flooding is an event or situation where an area or land is submerged due to an increased volume of water. Flood disaster education is one of the efforts to overcome flood disasters which often occur in the environment around SMA Negeri 14 Semarang, a school located in North Semarang District, Semarang city. North Semarang District is a district that is prone to flood disasters. Based on this, the aim of this research is to identify knowledge about flood disasters on students' environmental awareness. This type of research uses a quantitative type of research with quantitative descriptive data analysis, then a quasi-experimental design using a one-shot case study. The results of the research show that students' knowledge of flood disasters is moderate and students' environmental awareness is good, this is because knowledge does not directly influence environmental awareness, because this is the perception of different individuals.